2016
DOI: 10.1002/car.2438
|View full text |Cite
|
Sign up to set email alerts
|

Children and Violence Interactions: Exploring Intimate Partner Violence and Children's Experiences of Responses

Abstract: While there is a growing research interest in the experiences of children exposed to intimate partner violence (IPV), the role of children's social networks, other than the role of mothers, has been little discussed. The aim of this article is to study older children's stories of how they, and the adults in their social networks, respond to IPV. More specifically, we are interested in how older children describe both their own responses when exposed to IPV and responses from adults. This article focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Having witnessed violent relationships between their parents since childhood, children tend to naturalize and reproduce this model in their own marital bonds. This finding is corroborated by a study carried out in Romania, which argues that children of couples living in violent relationships are more likely to repeat this behavior in their future relationships (11) .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Having witnessed violent relationships between their parents since childhood, children tend to naturalize and reproduce this model in their own marital bonds. This finding is corroborated by a study carried out in Romania, which argues that children of couples living in violent relationships are more likely to repeat this behavior in their future relationships (11) .…”
Section: Discussionsupporting
confidence: 52%
“…Authors further posit that these aggressive behaviors are used, even if implicitly, as a method of domination, entailing different phases (11) In a study carried out in Brazil, authors describe the cycle of violence as beginning in a phase of accumulation of tension and small misunderstandings, of a more psychological and moral character; in turn, there are brief episodes of lack of control, with the occurrence of physical aggression and / or situations considered more serious; finally, there is the phase of reconciliation and promises of change (14) . The discourse of men also reveals that the fact that the aggravation is cyclical in the relationship, with alternation of violent episodes and peaceful moments, creates the idea that that moment was fleeting.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of a larger project on social network responses to children exposed to IPV. 1 Within the framework of this major project, interviews were conducted with children, mothers, relatives and social workers ( Akerlund and Sandberg, 2016;Hyd en, 2016;Sandberg, 2016) as the project was inspired by a systemic approach to IPV (cf. Vetere and Cooper, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…While the role of the informal networks of adult IPV victims has been relatively well explored, researchers have only in recent years begun to take an interest in how informal networks respond to children exposed to IPV (Åkerlund and Sandberg, ; Miller and others, ; Sandberg, ). This literature primarily focuses on adult network members and, for instance, shows that the presence of extended adult family members in the home may influence children positively by reducing their internalising and externalising adjustment problems following exposure to violence (Miller and others, ).…”
Section: Introductionmentioning
confidence: 99%
“…The paper illustrates that responses were highly interactional and that the ways in which children responded affected how the adults around them responded. Åkerlund and Sandberg's (, p. 54) analysis showed that ‘children who position themselves, and are positioned, as competent and adult‐like do not receive immediate support and protection’ and may not be regarded as a vulnerable victim; ‘whereas children who are perceived as vulnerable and positioned as incompetent to make decisions about their own lives receive adults' preferred support’, yet their own agency may be overlooked. The research findings also suggested that there are children who are positioned as both competent and vulnerable, which appears to be related to their ability to disclose and communicate their needs.…”
Section: Young People and Intimate Partner Violencementioning
confidence: 99%